Social Change and Crime Rates in Puerto Rico - Arthur, John A. (International journal of offender therapy and comparative criminology, 1992)
This report examines crime trends and patterns in Puerto Rico and assesses the effects of selected measures of social change in explaining crime on the island using data from the Uniform Crime Reports and the International Police Organization. It is concluded that violent and property crime levels are rising even though property crimes have increased at a faster pace than violent crimes. The data showed that the 1970's were characterized by low crime rates compared to the period after 1980. Burglary, the major property crime for the first 15 years of the period covered, has been replaced in the last two years by larceny-theft, while robbery and aggravated assault are the most frequently committed violent offenses. The results of the regression analysis revealed that overall, the measures of social change were very effective in predicting both violent and property crime rates in Puerto Rico